How do technique and coordination change during learning of a whole-body task: Application to the upstart in gymnastics? - Hiley, M. J.; Schmid, N.; Yeadon, M. R. (Journal of Sports Sciences, 2019)
When learning swinging skills on a bar there has been conflicting advice in the research literature regarding whether to coach the "gold standard" technique to novices. The present study aimed to determine how technique (joint angle time histories) and (inter-limb) coordination changed as novice gymnasts learned a fundamental gymnastics skill (the upstart). It was hypothesised that both technique and coordination would become more like an expert as learning progressed. Eight novice gymnasts, unable to perform an upstart, underwent four months of training, with the number of successful upstarts out of 10 recorded at the start and then every month subsequently. In the first and last sessions motion capture was used to determine joint kinematics. Root mean squared differences for the joint angle time histories and continuous relative phase at the shoulder and hip were calculated between the novices and an expert gymnast. As training progressed technique and coordination became more like the expert gymnast. The more successful novices were better able to time their actions within the swing than the less successful novices. Gymnastics coaches teach towards a "gold standard" technique since being successful at the skill is not the only goal, as considerations for future skill development are made.